EFECTO DE LA REFRIGERACIÓN SOBRE LA MOTILIDAD, INTEGRIDAD DE MEMBRANA ACROSOMAL Y REACCIÓN ACROSOMAL EN ESPERMATOZOIDES CANINOS - Manosalva P., Iris (2005)
Preservation methods of spermatozoa using refrigeration have been developed for canine sperm; however, the rate of fertilization is still low, possibly due to cell damage for unknown reasons. The objective of this study was to evaluate the effect of refrigeration upon motility, mitochondrial activity, acrosomal membrane integrity, and acrosomal reaction in dog sperm incubated in three culture media (Ferp Talp, CCMm, Sp Talp) using new methodologies (Mito Tracker, Lyso Tracker, SBTI). The results indicated that exist a significant decrease (p<0.05) in motility, mitochondrial activity, and acrosomal membrane integrity in refrigerated sperm in comparison with fresh sperm. Also, the dynamic of acrosomal reaction was different in refrigerated sperm in comparison with fresh sperm. The Sp Talp and CCMm media showed the best results in holding the mitochondrial activity and acrosomal membrane integrity.